Influência da incorporação da lama de alto forno em massa cerâmica para a produção de telhas - COSTA, Roberta Lima de Souza (Universidade Federal do Pará, 2018)
The use of residues in the clay-based ceramic composition for the production of ceramics has been widely studied, since a significant improvement in the chemical and physical properties of the final materials has been observed. The aim of this work is to evaluate the influence of the incorporation of 5 and 10 wt. % of blast furnace sludge into the clay slag, both from the state of Pará. The raw material and the waste were initially benefited in order to reduce the particle size and subsequently passed through a sieve with a mesh opening equal to #325. After this step, the residue and the raw material were submitted to FRX, EDS, XRD, TG / DTG, particle size distribution, MO, SEM and determination of plasticity and liquidity limits. Test specimens were prepared by uniaxial pressing of 20 Mpa for burning in a muffle-type laboratory oven at temperatures of 750, 850 and 950oC. MEA, PA, AA, RLQ and three-point flexural strength were evaluated. The microstructure of the burnt ceramics was evaluated by OM, MEV and XRD. The results showed that the blast furnace slurry consists predominantly of iron compounds, which contributes to the reddish placement in the sintered part. The residue presents a granulometry favorable to the addition in clayey mass, not altering the technological properties. Thus, it was concluded that the composition with addition of 5% of blast furnace sludge was the one that presented favorable results and required by standards for the manufacture of tiles.